Long term stability of the subcutaneous cardioverter defibrillator implanted by means of the intermuscular two incision technique. (24th May 2021) - Bisignani, G; Bisignani, A; Cavaliere, AL; Lovecchio, M; Valsecchi, S; De Bonis, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background To ensure effective defibrillation with the subcutaneous implantable cardioverter defibrillator (S-ICD), both the lead and the generator must be adequately positioned extrathoracically. We assessed the long-term adequacy of the S-ICD system position and its stability in a group of patients who received the S-ICD by means of the two-incision intermuscular technique. Methods The PRAETORIAN score uses chest radiography to provide feedback on S-ICD positioning, and identifies patients with high defibrillation thresholds. We compared radiographs taken immediately after implantation and on 12-month follow-up examination. Results We analyzed data from 38 patients with the S-ICD generator positioned in an intermuscular pocket. The median PRAETORIAN score was 38 [25th to 75th percentile: 30 to 60]. Two (5%) patients had a score of 90 (intermediate risk of conversion failure). The thickness of the adipose tissue between the coil and the sternum was ≤1 coil width in 72% of patients, the generator was on, or posterior to, the midline in 94% of patients, and the amount of fat tissue between the generator and the thoracic wall was less than the generator width in 78% of patients. No generator or electrode dislodgments were detected on analyzing radiographs collected at the 12-month visit. In all patients, assessment of the PRAETORIAN score confirmed the values calculated on post-implantation analysis. During follow-up, no ineffective therapies, sudden cardiac or device-related deaths occurred. Conclusions The position of the S-ICD system implanted using the two-incision intermuscular technique was adequate at the time of implantation and remained stable after 12 months.